Randomized controlled study of the impact of a participatory patient care plan among primary care patients with common chronic diseases: a one-year follow-up study - Nina Tusa; Hannu Kautiainen; Pia Elfving; Sanna Sinikallio; Pekka Mäntyselkä (BMC, 2021)
Abstract Backround Chronic diseases and multimorbidity are common in the ageing population and affect the health related quality of life. Health care resources are limited and the continuity of care has to be assured. Therefore it is essential to find demonstrable tools for best treatment practices for patients with chronic diseases. Our aim was to study the influence of a participatory patient care plan on the health-related quality of life and disease specific outcomes related to diabetes, ischemic heart disease and hypertension. Methods The data of the present study were based on the Participatory Patient Care Planning in Primary Care. A total of 605 patients were recruited in the Siilinjärvi Health Center in the years 2017-2018 from those patients who were followed up due to the treatment of hypertension, ischemic heart disease or diabetes. Patients were randomized into usual care and intervention groups. The intervention consisted of a participatory patient care plan, which was formulated in collaboration with the patient and the nurse and the physician during the first health care visit. Health-related quality of life with the 15D instrument and the disease-specific outcomes of body mass index (BMI), low density lipoprotein cholesterol (LDL-C), hemoglobin A1c (HbA1C) and blood pressure were assessed at the baseline and after a one-year follow-up. Results A total of 587 patients with a mean age of 69 years were followed for 12 months. In the intervention group there were 289 patients (54% women) and in the usual care group there were 298 patients (50% women). During the follow-up there were no significant changes between the groups in health-related quality and disease-specific outcomes. Conclusions During the 12-month follow-up, no significant differences between the intervention and the usual care groups were detected, as the intervention and the usual care groups were already in good therapeutic equilibrium at the baseline. Trial registration ClinicalTrials.gov Identifier: NCT02992431 . Registered 14/12/2016